Examining the Impact of School Esports Program Participation on Student Health and Psychological Development - Trotter, Michael G.; Coulter, Tristan J.; Davis, Paul A.; Poulus, Dylan R.; Polman, Remco (Frontiers in Psychology, 2022)
This study examined the influence of 7 high school esports developmental programs on student self-regulation, growth mindset, positive youth development (PYD), perceived general health and physical activity (PA), and sport behaviour. 188 students (male n = 120; female n = 68) originally participated (89 enrolled in an esports program in their school and 99 acted as matched controls), with 58 participants (n = 19 esports group; n = 39 controls) completing both pre- and post-program information. At baseline, no significant differences were found between youth e-athletes and their age matched controls. The analysis for the observation period showed a significant interaction effect for the PYD confidence scale, with post-hoc comparisons showing a significant decrease in the control group from pre- to post assessment whereas the esports group remained the same. Time main effects showed a decrease in the self-regulation motivation factor, PYD connection factor and PA for all participants. Overall, this study showed that students enrolled in their respective school esports program did not differ from those who did not in self-regulation, growth mindset, PYD, perceived health and PA, and sport behaviour. It was likely that all participants showed a decrease in motivation, connection, and PA due to COVID19 lockdown during the study period.